In-hospital care of children with COVID‐19 - Oi-Wa Chan; En-Pei Lee; Cheng-Che Chou; Shen-Hao Lai; Hung-Tao Chung; Jung Lee; Jainn-Jim Lin; Kai-Sheng Hsieh; Shao-Hsuan Hsia (Elsevier, 2024)
Children have been reported to be less affected and to have milder severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection than adults during the coronavirus disease 2019 (COVID-19) pandemic. However, children, and particularly those with underlying disorders, are still likely to develop critical illnesses. In the case of SARS‐CoV‐2 infection, most previous studies have focused on adult patients. To aid in the knowledge of in-hospital care of children with COVID‐19, this study presents an expert review of the literature, including the management of respiratory distress or failure, extracorporeal membrane oxygenation (ECMO), multisystem inflammatory syndrome in children (MIS-C), hemodynamic and other organ support, pharmaceutical therapies (anti-viral drugs, anti-inflammatory or antithrombotic therapies) and management of cardiopulmonary arrest.